2022
DOI: 10.3390/membranes12020239
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Antimicrobial Cellulose/Chitosan/ZnO Biodegradable Composite Membrane

Abstract: In this study, chitosan and sugarcane cellulose were used as film-forming materials, while the inorganic agent zinc oxide (ZnO) and natural compound phenyllactic acid (PA) were used as the main bacteriostatic components to fabricate biodegradable antimicrobial composite membranes. The water absorption and antimicrobial properties were investigated by adjusting the concentration of PA. The scanning electron microscopy (SEM), Fourier transform infrared spectroscopy (FTIR) and X-ray diffraction (XRD) results demo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 59 publications
(62 reference statements)
1
7
0
Order By: Relevance
“…50 Different results were found by Sun et al, who fabricated of Cellulose/Chitosan/ZnO/PA composite membranes and demonstrated good antifungal activity against A. niger. 51…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…50 Different results were found by Sun et al, who fabricated of Cellulose/Chitosan/ZnO/PA composite membranes and demonstrated good antifungal activity against A. niger. 51…”
Section: Resultsmentioning
confidence: 99%
“…50 Different results were found by Sun et al, who fabricated of Cellulose/ Chitosan/ZnO/PA composite membranes and demonstrated good antifungal activity against A. niger. 51 On the other hand, Bailore et al demonstrated that the antifungal activity is affected by the formation of nanoclusters in the polymer matrix, they made pullulan/collagen blend film with dopant ZnO nanoparticles and tested the antifungal activity against A. niger, their films showed excellent antifungal activity with a zone 18 mm maximum inhibition for pullulan/collagen/ ZnONps (0.5%), they attribute this behavior to the fact that ZnONps affect the cellular functions of the fungus by increasing the nucleic acid content. The lowest concentration used in the test of nano ZnO (0.25%) was not effective enough, while the concentration of nano ZnO (1%) might have agglomerated and would have resulted in inefficient penetration into the fungal cells.…”
Section: Antimicrobial and Antifungal Propertiesmentioning
confidence: 99%
“…b. The nanoparticles carried on cellulose membrane [19]. The composite membrane was cut into discs with a diameter of 6 mm, and the antimicrobial activity was evaluated by measuring the inhibition zone surrounding each disc.…”
Section: Antibiotic Performancementioning
confidence: 99%
“…Chitosan (CS) is a linear polysaccharide with N-acetyl-D-glucosamine and D-glucosamine units, used in biomedical applications, due to its remarkable properties, such as its hydrophilicity, biodegradability, biocompatibility, and low cost [ 13 , 14 , 15 , 16 ]. Chitosan is a polysaccharide derived from chitin [ 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%